Pengaruh Pengungkapan Sustainability Report dan Intensitas Modal terhadap Profitabilitas: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Radinkha Tiara Aurelya; Efrizal Syofyan (Universitas Negeri Padang, 2023)
This study aims to determine the effect of sustainability report disclosure and capital intensity on profitability. The population on this research is several manufacturing company listed on Indonesian Stock Exchange start from 2016-2020. This study used secondary data. The sampling technique used purposive sampling method with 105 firm as the sample during 5 years period. Using panel data regression analysis as data analysis technique on this research. The result showed that capital intensity had an effect on firm profitability. Meanwhile, sustainability report disclosure has no effect on firm profitability.